2019
DOI: 10.1007/978-3-030-05728-2_1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Current and Power Distributions in a Submerged Arc Furnace

Abstract: Most submerged arc furnaces used for the production of ferroalloys run on three-phase alternating current. This affects the electrical operation of the furnace and thus it is of interest to study alternating current distributions in the system. This work presents computations of alternating electric current distributions inside an industrial submerged arc furnace for silicon production. A 3D model has been developed in ANSYS Maxwell using the eddy current solver. In each phase, electrode, central arc, crater, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In this paper, we have considered the same industrial furnace as reported in [11,12,15] that is operating with an AC frequency of 50 Hz and its schematic diagram is shown in Fig. 1, which is adapted from [11].…”
Section: Furnace Geometry and Materials Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, we have considered the same industrial furnace as reported in [11,12,15] that is operating with an AC frequency of 50 Hz and its schematic diagram is shown in Fig. 1, which is adapted from [11].…”
Section: Furnace Geometry and Materials Propertiesmentioning
confidence: 99%
“…The FE model of the furnace partitioned into different zones with different electrical conductivities. Tesfahunegn et al [11,12] developed a 3D numerical furnace model that contains electrodes, main arcs, side arcs, crater-wall, crater, and other parts using ANSYS Fluent electric potential solver (DC). The authors reported results for current distribution for a range of arcing configurations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation